Multiplicidades de resoluções de alunos do ensino médio em problemas abertos de matemática - Dalto, Jader Otavio; Santos, João Ricardo Viola Dos [UNESP]; Buriasco, Regina Luzia Corio De [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2017)
This article investigates how students from basic education deal with open-ended mathematics problems. To achieve this objective, six open-ended mathematics problems were applied in two classes of the 9th grade of elementary school and in two classes of the 3rd year of high school. By means of a qualitative research, it was analyzed the students’ multiplicity of resolutions and it were evidenced their singularities. The analysis showed a variety of strategies presented by students to solve problems. These strategies are very unique, developed by idiosyncratic ways of the students to read the statements of the problems, implement a way to deal with them and construct a settlement process. Facing these singularities, it was identified a variety of resolutions, several different ways by which the students solve problems. To solve open-ended mathematics problems, the mathematical activity of the students occurs by means of processes that are often little observed by teachers. In this direction, the analysis of written production shows up as a possibility to look for ways how students deal with mathematics problems, not characterizing them by punctuating what they didn’t or what they should have done.

Investigam-se maneiras de lidar de alunos da educação básica com problemas abertos de matemática. Para isso, seis problemas abertos de matemática foram aplicados em duas turmas do 9º ano do ensino fundamental e duas turmas do 3º ano do ensino médio de uma escola pública. Por meio de uma abordagem qualitativa de pesquisa, analisou-se a multiplicidade das resoluções dos alunos e evidenciaram-se suas singularidades. A análise mostrou uma variedade de estratégias apresentadas pelos alunos ao resolverem os problemas. Essas estratégias são muito singulares, elaboradas por modos idiossincráticos de os alunos lerem o enunciado do problema, implementarem uma maneira de lidar com ele e construírem um processo de resolução. Diante dessas singularidades, foi identificada uma multiplicidade de resoluções, diversos e diferentes modos de resolução dos problemas. Ao resolverem problemas abertos, a atividade matemática dos alunos se dá por meio de processos que são, muitas vezes, pouco observados pelos professores. Nessa direção, a análise da produção escrita mostra-se como possibilidade de olhar para as maneiras de lidar dos alunos, de modo a não caracterizá-los pela falta, pontuando o que não foi feito ou aquilo que deveria ter sido feito.
Multiplicities of resolutions by high school students in open-ended mathematics problems
Keywords: mathematics education; assessment as a research practice; written production analysis; educação matemática; avaliação como prática de investigação; análise da produção escrita